2023
DOI: 10.3390/neurolint15010017
|View full text |Cite
|
Sign up to set email alerts
|

Migraine Disability Improvement during Treatment with Galcanezumab in Patients with Chronic and High Frequency Episodic Migraine

Abstract: Background: The aim of the present study was to assess the migraine outcome, in particular migraine disability, in chronic (CM) and high frequency episodic migraine (HFEM) patients in treatment with galcanezumab. Methods: The present study was conducted at the Headache Centre of Spedali Civili of Brescia. Patients were treated with galcanezumab 120 mg monthly. Clinical and demographical information were collected at the baseline (T0). Data about outcome, analgesics consumption and disability (MIDAS and HIT-6 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
(63 reference statements)
0
0
0
Order By: Relevance
“…The observed amelioration in MHDs and MMDs in our current study aligns with other real-world studies on galcanezumab, indicating a more extensive improvement in MHDs and MMDs than reported in randomized controlled trials RCTs ( 18 , 46 48 ). Notably, in both CM and EM patients, the correlation between MMDs and scores on the MIDAS and the HIT-6 was reported to be stronger during galcanezumab treatment than their correlation recorded at baseline.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The observed amelioration in MHDs and MMDs in our current study aligns with other real-world studies on galcanezumab, indicating a more extensive improvement in MHDs and MMDs than reported in randomized controlled trials RCTs ( 18 , 46 48 ). Notably, in both CM and EM patients, the correlation between MMDs and scores on the MIDAS and the HIT-6 was reported to be stronger during galcanezumab treatment than their correlation recorded at baseline.…”
Section: Discussionsupporting
confidence: 91%
“…Other real-world studies also indicated that monthly prophylactic treatment with galcanezumab was effective in both CM and EM, especially in reducing migraine burden and disability with significant improvements in several PROMs, including HIT-6, MIDAS, and MSQ ( 18 , 46 ). In this study, the median MIDAS scores started at 50.0 at baseline, then decreased to 9.0 by the 3rd month, indicating a shift from “severe disability” to “little or no/mild” disability.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Migraine represents one of the most severe and prevalent brain conditions [ 1 ]. Its physiopathology is characterized by two opposing processes, habituation and sensitization, that together determine the cycle of a migraine attack [ 2 ].…”
Section: Introductionmentioning
confidence: 99%